THE INFLUENCE OF IN STORE DISPLAY, IMPULSE BUYING, AND PERSONAL SELLING ON PURCHASE DECISION IN FASHION SITI COLLECTION MSMEs - Fani Fadila Habsari; Indah rahayu (LPPM Universitas An Nuur, 2024)
Background : The ready to wear garment industry requires a high level of innovation from its players so that it can continue to attract consumers to buy various kinds of clothing products that are available in various models. Clothes seem to be a mandatory hunt when shopping, apart from protecting themselves, humans need clothes for their existence in the world of fashion. The increasing number of clothing models is a challenge for business people, how to ensure that purchase decisions continue to increase.Purpose: Based on the background and problem formulation that has been explained, the aim of this research is to analyze the influence of in-store displays on impulse buying in Siti Collection fashion MSMEs, to analyze the influence of in store displays on personal selling in Siti Collection fashion MSMEs, to analyze the influence of impulse buying on purchase decisions in Siti Collection fashion MSMEs, to analyze the influence of personal selling on purchase decisions in Siti Collection fashion MSMEs.Method: This research uses a quantitative approach method. The sample used in this research was 95 respondents using probability sampling techniques including random sampling techniques. Data analysis uses the Partial Least Square (PLS) statistical analysis technique.Conclusion: in store displays, impulse buying, and personal selling have an influence on purchase decisions Suggestion For future research, we can add the variables price discount, lifestyle, product quality, service quality, consumer behavior, promotion as moderating variables that can improve purchase decisions